Lipopeptide PAM3CYS4 Synergizes N-Formyl-Met-Leu-Phe (fMLP)-Induced Calcium Transients in Mouse Neutrophils. Issue 4 (October 2018) - Ding, Renyu; Xu, Ganqiong; Feng, Yan; Zou, Lin; Chao, Wei
Abstract : ABSTRACT: N-Formyl-Met-Leu-Phe (fMLP), a mimic of N-formyl oligopeptides that are released from bacteria, is a potent leukocyte chemotactic factor. It induces intracellular calcium ([Ca 2+ ]i) transient that is important for various neutrophil biological functions, e.g., adhesion, ROS, and cytokine productions. Toll-like receptors (TLRs), an essential part of host innate immunity, regulate neutrophil activities, but their role in [Ca 2+ ]i signaling is less clear. In the present study, we examined the effect of several TLR ligands, including Pam3Cys4 (TLR1/2), lipopolysaccharide (LPS, TLR4), and lipoteichoic acid (LTA, TLR2/6), on calcium signaling and on the fMLP-induced [Ca 2+ ]i transients in mouse neutrophils loaded with Fura-2/AM. We found that unlike fMLP, the three TLR ligands tested did not elicit any detectable Ca 2+ flux. However, Pam3Cys4, but not LPS or LTA, markedly synergized the fMLP-induced [Ca 2+ ]i transients, and had no effect on the host component keratinocyte-derived cytokine (KC)- or C5a-induced calcium flux. The effect of Pam3Cys4 on the fMLP-induced [Ca 2+ ]i transients is by enhancing extracellular Ca 2+ influx, not intracellular Ca 2+ release. Surprisingly, deletion of TLR2 or MyD88 in neutrophils had no impact on the Pam3Cys4's effect, suggesting a TLR2-MyD88-independent mechanism. Finally, using the pan PKC activator and inhibitor, we demonstrated that PKC negatively regulated fMLP-induced [Ca 2+ ]i transients and that inhibition of PKC did not prohibit Pam3Cys4's synergistic effect on the fMLP-induced calcium influx. In conclusion, the present study identified a novel synergistic effect of Pam3Cys4 on fMLP-induced [Ca 2+ ]i transients, a process important for many neutrophil biological functions.